PENGELOLAAN SUMBER DAYA MANUSIA BERBASIS PENILAIAN DAN PENGHARGAAN PADA PROGRAM KELURAHAN LENGKAP - Rizki Febrian Hamdani; Slamet Wiyono; Dwi Wulan Pujiriyani (Fakultas Politik Pemerintahan IPDN, 2022)
Abstract Human resources are very important on the organization's efforts to achieve goals. Success in implementing the human resources management function is the basis for improving the performance of team members and organizational performance. This paper analyzes the practice of assessing and reward-based human resource management and their influence in supporting the achievement of the Kelurahan Lengkap Program at the Land Office of Kediri City. This paper uses a qualitative method. The type of qualitative method used is a case study. The research was conducted in 10 May-15 June 2021. Primary data was obtained through observation and interviews, while secondary data was obtained through document studies related to the implementation of the Kelurahan Lengkap Program in Kediri City. The results showed that human resources in the Kelurahan Lengkap Program were managed by applying appraisals and reward approach. This is practiced with a reward system for implementing officers who are considered to have loyalty and perform well. There are four main factors that influence HR management, namely the bureaucratic structure, the resource, the attitude of the implementor and the communication model. The implementation of the Kelurahan Lengkap Program has been running quite effectively with the management of human resources carried out by the Land Office of the City of Kediri. However, there are resource factors that must be considered so that performance can run more optimally. Keywords: Kediri, policy performance, human resource managemen, policy implementation